ISO 9001: 2015 en universidades públicas en México; La calidad de información y el compromiso de la dirección. - González, Jesús Solís; Abreu, José Luis; Vázquez, María de Jesús Araiza (Revista Daena: International Journal of Good Conscience)
In this article, we will seek to analyze the role of information quality as a priority for the implementation of an ISO 9001 quality management system. The objective of this research is to analyze the quality of the information in relation to the management's commitment. An objective of this research is to analyze the level of adequacy of management systems ISO-9001 requirements regarding the quality information in the processes. This research is descriptive, quantitative, not experimental and correlational. This type of study aims to understand the degree of association that exists between two or more concepts, categories or variables in a particular context. An instrument with closed and mixed questions was applied, preceded of invitation letter, objective of the survey, respondent subject, questions and general data. The validity of the instruments was determined with Cronbach's alpha and a simple regression analysis was performed.